From Concept to Crystals via Prediction: Multi‐Component Organic Cage Pots by Social Self‐Sorting. (24th September 2019) - Greenaway, Rebecca L.; Santolini, Valentina; Pulido, Angeles; Little, Marc A.; Alston, Ben M.; Briggs, Michael E.; Day, Graeme M.; Cooper, Andrew I.; Jelfs, Kim E.
Abstract: We describe the a priori computational prediction and realization of multi‐component cage pots, starting with molecular predictions based on candidate precursors through to crystal structure prediction and synthesis using robotic screening. The molecules were formed by the social self‐sorting of a tri‐topic aldehyde with both a tri‐topic amine and di‐topic amine, without using orthogonal reactivity or precursors of the same topicity. Crystal structure prediction suggested a rich polymorphic landscape, where there was an overall preference for chiral recognition to form heterochiral rather than homochiral packings, with heterochiral pairs being more likely to pack window‐to‐window to form two‐component capsules. These crystal packing preferences were then observed in experimental crystal structures. Abstract : Selbstsortierte organische Käfigstrukturen („cage pots") wurden von der Molekülstruktur bis zum Festkörper computerchemisch vorhergesagt und anschließend synthetisiert. Die Moleküle entstehen durch soziale Selbstsortierung eines tritopen Aldehyds mit einem tritopen und einem ditopen Amin, ohne dabei eine orthogonale Reaktivität oder Vorstufen gleicher Topizität zu nutzen.